Inclusive Leadership and New Generation Employee Engagement: Investigating the Mediating Role of Procedural Justice and the Impact of Psychological Diversity Climate (International Journal of Food and Nutritional Sciences, 2022)
This study investigates the link between inclusive leadership and employee engagement among workers belonging to the GenZ and Millennial generations. The function of procedural fairness and the implications of having a psychologically diverse workforce are the specific topics that will be discussed. When working in a varied environment like the one we have today, it is essential to have leaders that are not just open and flexible but also have an understanding for other points of view. In this research, the influence of the emergence of Generation Z workers, as well as the distinct objectives and points of view of this generation, are investigated. When referring to the manner in which workers evaluate the fairness of a company's decision-making process, the phrase "procedural fairness" is used. The purpose of this article is to investigate the possibility that procedural fairness might significantly contribute to the advancement of inclusive leadership practices and the enhancement of employee engagement. The phrase "psychological diversity climate" refers to the way in which the general public sees the manner in which a firm addresses diversity management and values, as well as the ways in which this perception might strengthen inclusive leadership. The purpose of this study is to compile the most promising studies on the dynamics and consequences of these dynamics for businesses that are interested in recruiting and retaining members of the Millennial and Gen Z generations. It is difficult for organizations, executives, and HR practitioners to keep up with the shifting demographics and cultural changes in the workforce in today's quickly changing business environment. This is a tremendous challenge for all of these groups. For the benefit of their workforce, they want to provide a working environment that is equitable, inclusive, and focused on performance.